Examination of the Value of Domestic Component Levels and the Weight of Company Benefits in High-Rise Building Projects (Journal of Civil Engineering Researchers, 2024)
In a construction project, various project management activities assist in achieving project goals in planning, procurement, implementation, and control. In the construction sector, the Ministry of Public Works and Public Housing (PUPR) has mandated that at least 30-85% of products used should be domestic, as measured by the Domestic Component Level (TKDN), and the maximum value for the Company Benefit Weight (BMP) should be 15%. When combined, the TKDN and BMP values should be at least 40%. This regulation aims to reduce product imports and boost the purchase of domestic products, which can significantly improve the national economy if consistently implemented. This study employs a quantitative analysis method using data such as material specifications, material/tool prices, worker wages, Work Unit Price Analysis (AHSP), and Cost Budget Plans (RAB). The calculation shows that the total value for the project is 81.85%, comprising 73.381% for TKDN and 8.43% for BMP. Therefore, it can be confirmed that the construction project of ITS Tower 2 Building in Surabaya complies with the Presidential Regulation of the Republic of Indonesia Number 12 of 2021 mandates meeting the minimum threshold of 40%.
Keywords: Domestic Component Level (TKDN); Company Benefit Weight (BMP); Building Projects; Company Benefits; Construction Projects